Tourist transformation: Towards a conceptual model - Pung, Jessica Mei; Gnoth, Juergen; Del Chiappa, Giacomo (Annals of tourism research, 2020)
Despite growing interest in transformative tourism and its benefits, there is not yet a precise understanding of tourist transformation. This study contributes to fill this research gap by reviewing the contexts where transformative tourism research has emerged, and the main theories employed. Through a multi-disciplinary approach, the paper discusses key dimensions of transformative tourism experiences. The discussion suggests that liminality, cultural shock and challenges faced at the destination initiate transformation by provoking peak episodes, dilemmas and new performances. Contextual stimuli can lead tourists to reflectively interpret the experience and acquire skills, values and knowledge, with consequences on attitude, habits, and behaviour. A tourist transformation model is created, which provides a conceptual foundation for future research, and is relevant for designing and marketing transformative tourism experiences. •We discuss what characterises transformation through a hermeneutic approach.•Liminality, cultural shock and challenges at the destination initiate change.•Peak episodes, dilemmas and performances lead to re-interpret the self and world.•Transformative tourism leads to adopting new practices and life-changing decisions.•First study to illustrate key dimensions of tourist transformation in a model